Employing Natural Language Processing as Artificial Intelligence for Analyzing Consumer Opinion Toward Advertisement - Sun, Huilin; Zafar, Muhammad Zeeshan; Hasan, Naveed (Frontiers in Psychology, 2022)
With the advent and integration of technology in business, marketers started investing in numerous media platforms to influence the consumer’s sentiments. Artificial intelligence has been proved as one of the innovative tools of digitalization to change consumer’s media habits. Owing to the growing trends of e-commerce, the traditional advertising model is insufficient. Therefore, advertisers are taking advantage of artificial intelligence technology to meet current requirements. Thus, a deeper understanding of product advertisement with reference to consumer sentiments and its implications need to be established. The current research depicts the contribution of artificial intelligence to analyze the consumers’ attention, cognition and emotion. The target product was Samsung Galaxy. Researcher of the current study has employed Shapiro’s (1994) Think-aloud procedure for data analysis. Tweets dataset was divided into two categories. For international consumers’ sentiments 30877 tweets whereas for Pakistani consumers’ sentiments tweets dataset was 26834. For data analysis, authors used Nvivo for generating theme. The Nvivo produced word cloud. The word cloud generated with Pakistani tweets revealed that consumer attachment with Samsung product is based on emotional and attention and the preferred features of Samsung products are linked with emotional and attention. In contrary to that rest of the world tweets unfolded that emotion, attention and cognition make consumer preferences while selecting Samsung products. This study is useful to the cellular companies for targeting across the world population. The consumer preference varies while selecting cell phones. This study will provide a better idea to cell phone companies for manufacturing consumer oriented cell phones to get better results. Moreover, future research should add more countries separate data and generate a comparative study between developed countries consumer and developing countries consumer preferences. In addition to companies with better insights of consumer can highlight the most attractive features of cell phone in their advertisements.